The interpersonal dynamics consultation in physical health settings: a model for reflective practice. (12th February 2019) - Li, Ching; Hillen, Thomas; Reiss, David; Kirtchuk, Gabriel; Scott, Sandra; Maier, Michael
SUMMARY: The interpersonal dynamics between patient and doctor remain a daily challenge for clinicians, and reflective practice is a tool that allows them better understanding of how patients engage with treatment. The interpersonal dynamics consultation is a form of group-based reflective practice for patients with difficult relational (interpersonal) styles. It includes the whole multidisciplinary team in a systematic consultation in order to arrive at new understanding and management plans for these patients. Interpersonal dynamics consultations have been used successfully for many years in mental healthcare, and this article has arisen from a project exploring their application in physical healthcare settings. The project works to promote effective working at the interface of physical and mental healthcare and facilitates the important translational work of making psychiatry and psychotherapeutic ideas applicable in a broader context. This article outlines the interpersonal dynamics consultation model and illustrates its use in three fictitious cases from different medical specialties. LEARNING OBJECTIVES: After reading this article you will be able to: describe the ways in which reflective practice is beneficial to clinical work describe the basic structure of the interpersonal dynamics consultation, including the four interpersonal perspectives recognise the types of cases where interpersonal dynamics consultation might be most useful. DECLARATION OF INTEREST: None.